Charting the Future of Digital Democracy: A Comprehensive Bibliometric and Systematic Review - Ali, Akhwan; Lubis, Sandi; Darlis, Muh Akbar Ali; Demak, Herman; Ikbal, Muhammad (Jurnal Noken: Ilmu-Ilmu Sosial, 2024)
This study aims to analyze the research landscape of digital democracy through a bibliometric analysis and systematic literature review of publications from 2019 to 2024. The research identifies key themes, methodologies, and trends in digital democracy studies and evaluates their temporal evolution across various geographical and cultural contexts. The study employs a mixed-method approach, combining bibliometric analysis using VOSviewer and Bibliometrix tools with a systematic review following PRISMA guidelines. The findings reveal that while digital technologies offer the potential for enhancing democratic participation, they also present challenges, such as spreading misinformation and unequal access to digital resources. The study highlights the need for interdisciplinary approaches to address the complexities of digital democracy comprehensively. This research contributes by comprehensively mapping digital democracy research, offering valuable insights for academics, practitioners, and policymakers. The study’s limitations include its focus on English-language publications and excluding non-peer-reviewed literature, which may limit the diversity of perspectives captured. Future research should broaden the scope by including multilingual publications and conducting deeper empirical investigations into digital democracy initiatives to enrich understanding and implementation strategies in the digital era.